1996
DOI: 10.1128/mcb.16.10.5477
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Biochemical Characterization of Mutations in the ATPase and Helicase Regions of the Upf1 Protein

Abstract: mRNA degradation is an important control point in the regulation of gene expression and has been linked to the process of translation. One clear example of this linkage is the nonsense-mediated mRNA decay pathway, in which nonsense mutations in a gene can reduce the abundance of the mRNA transcribed from that gene. For the yeast Saccharomyces cerevisiae, the Upf1 protein (Upf1p), which contains a cysteine-and histidine-rich region and nucleoside triphosphate hydrolysis and helicase motifs, was shown to be a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
277
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(299 citation statements)
references
References 59 publications
19
277
3
Order By: Relevance
“…Previous results demonstrated that the Hcs2/Hel1p/ Mtt1p exhibited 59 r 39 DNA helicase activity (Biswas et al+, 1995;Bean & Matson, 1997)+ We have observed RNA-dependent ATPase activity in vitro, supporting a role for Mtt1p in RNA-dependent processes (data not shown), demonstrating that, like the Upf1 protein from this family, Mtt1 has both DNA-and RNA-dependent ATPase activity in vitro (Czaplinski et al+, 1995, Weng et al+, 1996a, 1996b)+ A comparison of the MTT1 and UPF1 genes identified several regions of similarity+ Both proteins contain a cysteine-histidine-rich region near the amino terminal end of the protein and harbor all of the motifs characteristic of a superfamily group I helicase (Fig+ 1)+ The primary sequences of the cysteinehistidine-rich regions of UPF1 and MTT1 are not very homologous; however, it is conceivable that these cysteine-histidine-rich regions form an unidentified type of cysteine-histidine-rich protein structure+ Interestingly, mutations in the cysteine-histidine-rich region of FIGURE 6. Mtt1p is associated with polyribosomes+ Polysome extracts of cells transformed with pG-1FLAGMTT1 were prepared and centrifuged through a 7-47% linear sucrose gradient+ An identical sample was treated with RNAse A and centrifuged in an identical manner+ A 254 was monitored as gradient fractions were collected+ The absorbance profiles are located at the top of each panel+ Total protein in each fraction was TCA precipitated and analyzed by SDS-PAGE followed by western blotting using anti-FLAG M2 monoclonal antibody as described previously (Czaplinski et al+, 1995)+ UPF1 have been shown previously to increase programmed Ϫ1 frameshifting efficiencies and promote nonsense suppression (Cui et al+, 1996;Weng et al+, 1996b)+…”
Section: The Mtt1p Is a Second Yeast Helicase That Interacts With Thesupporting
confidence: 62%
See 3 more Smart Citations
“…Previous results demonstrated that the Hcs2/Hel1p/ Mtt1p exhibited 59 r 39 DNA helicase activity (Biswas et al+, 1995;Bean & Matson, 1997)+ We have observed RNA-dependent ATPase activity in vitro, supporting a role for Mtt1p in RNA-dependent processes (data not shown), demonstrating that, like the Upf1 protein from this family, Mtt1 has both DNA-and RNA-dependent ATPase activity in vitro (Czaplinski et al+, 1995, Weng et al+, 1996a, 1996b)+ A comparison of the MTT1 and UPF1 genes identified several regions of similarity+ Both proteins contain a cysteine-histidine-rich region near the amino terminal end of the protein and harbor all of the motifs characteristic of a superfamily group I helicase (Fig+ 1)+ The primary sequences of the cysteinehistidine-rich regions of UPF1 and MTT1 are not very homologous; however, it is conceivable that these cysteine-histidine-rich regions form an unidentified type of cysteine-histidine-rich protein structure+ Interestingly, mutations in the cysteine-histidine-rich region of FIGURE 6. Mtt1p is associated with polyribosomes+ Polysome extracts of cells transformed with pG-1FLAGMTT1 were prepared and centrifuged through a 7-47% linear sucrose gradient+ An identical sample was treated with RNAse A and centrifuged in an identical manner+ A 254 was monitored as gradient fractions were collected+ The absorbance profiles are located at the top of each panel+ Total protein in each fraction was TCA precipitated and analyzed by SDS-PAGE followed by western blotting using anti-FLAG M2 monoclonal antibody as described previously (Czaplinski et al+, 1995)+ UPF1 have been shown previously to increase programmed Ϫ1 frameshifting efficiencies and promote nonsense suppression (Cui et al+, 1996;Weng et al+, 1996b)+…”
Section: The Mtt1p Is a Second Yeast Helicase That Interacts With Thesupporting
confidence: 62%
“…The results presented here describe a potential cellular role for the Mtt1p, a previously characterized helicase with significant homology to the Upf1p, a factor involved in regulating both translation termination and NMD (Czaplinski et al+, 1995(Czaplinski et al+, , 1998Weng et al+, 1996aWeng et al+, , 1996bWeng et al+, , 1998+ Evidence is presented indicating that Mtt1p is a second member of the Upf1-like family of helicases and has a role in modulating translation termination+ Interestingly, comparison of the MTT1 gene with other superfamily group I helicases identified unique features that tag this as a specific subfamily of superfamily group I helicases, possibly being involved in either RNA-dependent or RNA/DNA-dependent processes (Fig+ 1)+ As will be discussed below, these results suggest that a subset of the superfamily group I (Upf1p family) of RNA helicases are involved in modulating the efficiency of the translation termination process+…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The D and E residues coordinate the ATP-associated Mg 2+ and activate the attacking water molecule, respectively [109,110]. Mutation of these residues reduces ATPase and helicase reactivity [111][112][113].…”
Section: Motif II (Walker B) [108]mentioning
confidence: 99%